2013
DOI: 10.1177/0011392113488486
|View full text |Cite
|
Sign up to set email alerts
|

Defining the conversation aboutShari’a: Representations in Australian newspapers

Abstract: Debates about Shari’a law and legal pluralism have come to the fore of political discourse in many western multicultural societies including Australia. The mass media, in particular newspapers, have been active in reporting on Shari’a related news items and in doing so, have made a significant contribution to shaping political debate across western nations from governmental to grassroots levels. Understanding how newspapers report on Shari’a will provide important insights into how political discourse about Is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The content analysis drew on the methodologies of Van Driel and Richardson (1988a;1988b) and Possamai et al (2013). The unit of analysis was every article published from September 2015 (which coincided with the pope's appeal for every parish to welcome one migrant family) to September 2016 containing the words 'migrant/s' and 'refugee/s'.…”
Section: Religious Rhetoric Refugees and Human Rights In Two Catholic Countriesmentioning
confidence: 99%
“…The content analysis drew on the methodologies of Van Driel and Richardson (1988a;1988b) and Possamai et al (2013). The unit of analysis was every article published from September 2015 (which coincided with the pope's appeal for every parish to welcome one migrant family) to September 2016 containing the words 'migrant/s' and 'refugee/s'.…”
Section: Religious Rhetoric Refugees and Human Rights In Two Catholic Countriesmentioning
confidence: 99%
“…I have here presented qualitative analysis of one specific, telling event, but what of a quantitative analysis of a series of cases? Possamai et al (2013) analysed articles from the five years following the Archbishop of Canterbury's famous lecture on 7 February 2008, which included backing for the introduction of Shari'a in Britain. In all, 696 articles and opinion pieces across the four main Sydney newspapers were analysed.…”
Section: Shari'a In Australia: a Sociological Case Studymentioning
confidence: 99%
“…Recent research (e.g. Hussein and Possamai, 2013; Possamai, 2014; Possamai et al, 2013; Roose and Possamai, 2015) has found that, in Australia overall, the subject of religious and legal pluralism is not allowed to be fully aired or debated in the public sphere, unless to show it in a negative light. This leads to the argument that although Australia is a multicultural and multi-faith society, it is not fully post-secular.…”
Section: Shari’a In Australia: a Sociological Case Studymentioning
confidence: 99%
“…Given that discursive forms can influence claim-making practices, we approached all the manuscripts in our population as “subjective” social facts— contra the ideal of “objective” reportage—as the basis for coding (cf. Possamai et al 2013) to capture the overall variation of the media discourse as it appeared in the dataset, inclusive of the perspectives of “experts,” lay-interviewees, and all other sources whether summarized or directly quoted. 4…”
Section: Methodsmentioning
confidence: 99%